Developing building information modelling (BIM) implementation model for project design team - Mohd, Suzila; Brahim, Juliana; Ahmad Latiffi, Aryani; Fathi, Mohamad Syazli; Harun, Aizul Nahar (Construction Research Institute Malaysia, 2017)
Building Information Modelling (BIM) is implemented by the project design team to overcome the insufficiency of information in project design, which leads to design changes and design clashes. However, it seems difficult for project design team to implement BIM and get the benefits from its implementation in the project design stage because they do not know the right way to implement BIM especially to the beginner. Therefore, this paper proposes a model called ‘BIM Implementation Model for Project Design Team’. A literature review was carried out to explore on adaptation of BIM in the project design stage and types of maturity model in construction field. Apart from that, several semi-structured interviews were conducted with project design team to explore potential improvements to increase BIM implementation in project design stage. Both data from the literature review and the semi-structured interviews are important and contributed to the development of ‘BIM Implementation Model for Project Design Team’.This model is created to assist the project design team to improve the implementation of BIM in the project design stage and getting benefits from its implementation. The model purposes, the concept of the model, procedure of its development as well as details of the model elements presented in this paper will form the basis for the development of the ‘BIM Implementation Model for Project Design Team’.